Anemia Associated with Student Learning Achievement: Cross-Sectional Study - Taqwin Taqwin; Eka Purwita sari; Asrawati Asrawati; Hadriani Hadriani; Henrietta Imelda Tondong; Siti Hadijah Batjo; Sri Yanti Kusika; Niluh Nita Silfia (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Adolescent anemia is one of the public health problems globally, including in Indonesia. Learning achievement is associated with adolescent anemia in girls. This study aims to determine the relationship between anemia and teenage girls' learning achievement at school. Methods: The type of research was a cross-sectional study conducted in June 2022 at one of the Aliyah madrasas in Palu City. Research samples from 34 adolescent girls were taken using a simple random technique. The research variables were learning achievement, body mass index (BMI), and hemoglobin levels. Research data was collected using observation sheets, digital weight scales, height using a longboard, and hemoglobin levels using the Easy Touch Kit. The measurement of learning achievement uses the average score of student education reports based on the minimum completeness criteria (CCM) set by the school with the requirements of good (B), enough (C), and less (K). The research data analysis used a chi-square test and prevalence ratio with a confidence level (95%). Results: The results showed that anemia in adolescent girls was 67.6%. There was an association between learning achievement and anemia (?=0.034) and PR value = 0.79, 95% CI 0.00 to 1.52. There was no association between body mass index and anemia (?=0.49) and PR value = 0.54, 95% CI 0.08 to 3.7. Conclusion: The study concluded that the percentage of anemia in adolescent girls was 67.6% and was categorized as a severe public health problem. Teenage girls who are anemic have a risk of 0.79 times having academic achievement with a grade of C. Students are expected to pay attention to adequate nutritional intake; the school facilitates regular iron supplementation intervention programs and nutrition education for vulnerable students, and health programs are integrated with the educational curriculum, health monitoring, and periodic anemia screening